Benefits of stereotactic ablative radiotherapy combined with incomplete transcatheter arterial chemoembolization in hepatocellular carcinoma. Issue 1 (December 2016) - Paik, Eun; Kim, Mi-Sook; Jang, Won; Seo, Young; Cho, Chul-Koo; Yoo, Hyung; Han, Chul; Park, Su; Kim, Sang; Kim, Young
Abstract Background This study aimed to evaluate the effect of stereotactic ablative radiotherapy (SABR) after incomplete transcatheter arterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) patients. Methods The study enrolled 178 HCC patients initially treated with TACE between 2006 and 2011. Patients were included if they had Barcelona Clinic Liver Cancer stage 0 or A, ≤3 nodules with a total sum of longest diameter ≤10 cm, Child-Turcotte-Pugh score of ≤7, no major vessel invasion, and no extra-hepatic metastases. Results Twenty-four patients achieved a complete response to TACE (group 1). Among those with incomplete response, 47 patients received other curative treatments (group 2), 37 received SABR (group 3), and 70 received non-curative treatments (group 4). The 2–year overall survival (OS) rates for groups 1, 2, 3, and 4 were 88 %, 81 %, 73 %, and 54 %, respectively. The corresponding 5-year OS rates were 50 %, 58 %, 53 %, and 28 %, respectively. Conclusions Patients treated with SABR after incomplete TACE had similar survival outcomes to those achieving complete response to TACE or receiving curative treatments. However, patients receiving non-curative treatments had significantly lower survival rates than the other groups. Therefore, if SABR was indicated at the initial diagnosis, it might be recommended after TACE failure.